THE URGENCY OF DEVELOPING THE NATIONAL ECONOMIC LEGAL SYSTEM IN THE ERA OF GLOBAL TRADE BASED ON PANCASILA VALUES - Amalia Galih Wangi (Universitas 17 Agustus 1945 Semarang, 2023)
Abstract: Indonesia is one of the countries that is struggling to attract as much investment as possible to build a national economic system to face challenges in the era of economic globalization. The development of a national economic legal system in the era of trade globalization is in accordance with the values of Pancasila. The problems that occur are related to the urgency of developing a national economic legal system in the era of trade globalization based on the values of Pancasila. The method used in this paper is normative legal research, namely through library research by studying books, and supported by field research by interviewing informants related to the subject of this paper. The results of the study show that the development of a national economic legal system in the era of globalization has a major role to play in providing opportunities for economic development to realize people's welfare. The urgency of developing a national economic law system in the era of trade globalization is based on the values contained in Pancasila and the 1945 Constitution of the Republic of Indonesia. The current era of trade globalization with the concept of a liberal economy in the global world cannot be fully and comprehensively applied in Indonesia, especially in implementing the formation of legislation in the field of economic law. Indonesia needs to reorganize the values of the people's economy, the agricultural economy, the Pancasila economy, and others that are protected by an effective legal system and are fully facilitated and fully supported by the state.